Navigating Jurisdictional Turbulence on Maritime and Civil Aviation Labour Claims in Nigeria: Federal High Court Versus National Industrial Court Controversies (Global Journal of Human-Social Science, 2024)
Controversies have trailed the frontiers of the civil jurisdictions of the Federal High Court [FHC] and National Industrial Court [NIC] since the bifurcation of the FHC's civil jurisdiction in favour of the NIC over labour matters by S. 254C of the Constitution, such that, both courts have been asserting rival jurisdictions on the same subject matter, with the consequence that, the purposes of conferring exclusive civil jurisdictions on both -specialization and efficiency -are being thwarted. While some of these controversies have been settled with the acceptance of the appellate decisions on them, the controversies regarding the frontiers of their mutually exclusive civil jurisdictions on admiralty/aviation labour causes have, however, remained intractable. With the recent Court of Appeal's decision in Bains' case [2021], confirming the NIC's exclusive civil jurisdiction on merchant shipping/civil aviation labour matters, it was thought, the contest had been rested, but it has instead, become more ferocious, as legal writers have joined the fray, majority of who vehemently disagreed with the Court of Appeal's decision.
Keywords: admiralty/maritime/merchant shipping; civil aviation/commercial aviation; labour/ employment disputes; jurisdiction